Ground Deformation Detected by Permanent Tiltmeters on Mt. Etna Summit: The August 23-26, 2018, Strombolian and Effusive Activity Case - Salvatore Gambino; Marco Aloisi; Giuseppe Di Grazia; Giuseppe Falzone; Angelo Ferro; Giuseppe Laudani (International Journal of Geophysics)
Over the last few years, three tilt deep stations (27-30 meters) have been set up in the summit area of Mount Etna volcano. The aim of this challenging project is to record the ground deformations of the summit craters activity with high precision. We considered data related to the August 23-26, 2018, Strombolian and effusive activity. In this case, tiltmeters recorded variations in the order of 10−7 radians, not observed at the other stations. These changes suggest a shallow contraction source just south of the Southeast Crater. This result, related to the volcanic tremor source, points to the presence of a gas/magma reservoir feeding the Strombolian activity at 1200 m above sea level.